Effects of INA on postharvest blue and green molds and anthracnose decay in citrus fruit - Jia-yi JING; Hong-yan ZHANG; Yao-bi XUE; Kai-fang ZENG (Journal of Integrative Agriculture)
As a synthetic functional analog of salicylic acid, 2,6-dichloroisonicotinic acid (INA) is effective in inducing the host disease resistance of a plant against a pathogen. The effects of INA on controlling postharvest blue and green molds and anthracnose decay and defense-related enzymes on citrus fruits were investigated, and the ascorbic acid of naturally infected citrus flavedo was also measured. Results showed that 1.0 mmol L−1 INA treatments significantly reduced blue and green molds and anthracnose decay development on both wound-inoculated fruit and naturally-infected fruit compared with the control fruit. The treatment effectively enhanced the β-1,3-glucanase (GLU), chitinase (CHI), phenylalanine ammonia-lyase (PAL) and peroxidase (POD) activities and the polyphenol oxidase (PPO) in flavedo. The results presented here suggest that INA might be used as a chemical fungicide substitution to control postharvest diseases in citrus fruits.